2019
DOI: 10.1111/php.13119
|View full text |Cite|
|
Sign up to set email alerts
|

Skin Microbiome Compositional Changes in Atopic Dermatitis Accompany Dead Sea Climatotherapy

Abstract: Dead Sea climatotherapy (DSC) is a well‐established therapeutic modality for the treatment of several diseases, including atopic dermatitis. Skin microbiome studies have shown that skin microbiome diversity is anticorrelated with both atopic dermatitis severity and concurrent Staphylococcus aureus overgrowth. This study aimed to determine whether DSC induces skin microbiome changes concurrent with clinical improvements in atopic dermatitis. We sampled 35 atopic dermatitis patients and ten healthy controls on b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 39 publications
1
27
0
3
Order By: Relevance
“…The community composition was similar on AD LS and NLS, despite clinically differences between the two sample sites. No signi cant association was found with neither AD disease severity (SCORAD), nor carriage of loss-of-function FLG mutations, as previously reported for the bacterial community on AD skin [5,19]. The present study con rms, that the eukaryotic microbial richness is signi cantly greater on AD skin compared to healthy control skin [8,9].…”
Section: Discussionsupporting
confidence: 69%
“…The community composition was similar on AD LS and NLS, despite clinically differences between the two sample sites. No signi cant association was found with neither AD disease severity (SCORAD), nor carriage of loss-of-function FLG mutations, as previously reported for the bacterial community on AD skin [5,19]. The present study con rms, that the eukaryotic microbial richness is signi cantly greater on AD skin compared to healthy control skin [8,9].…”
Section: Discussionsupporting
confidence: 69%
“…These findings indicate that AD pathogenesis has an impact on the overall skin microbiota, comprising staphylococcal species, independent of the presence of eczema. The presence of a universal bacterial community within AD skin sites has also previously been suggested [ 8 , 11 ], and Brandwein et al found that increasing AD severity, rather than the presence or absence of lesions, was most important regarding changes in bacterial community within AD skin compared to healthy skin [ 11 ]. The present study of species-level characterization of Staphylococcus further supports this theory.…”
Section: Discussionmentioning
confidence: 90%
“…Yet, reduced alpha diversity may not be universal, but depend on S. aureus skin colonization [ 4 , 6 ] and the microenvironmental skin conditions, such as moisture and sebum content [ 7 , 8 ]. Some studies have found that alpha diversity is significantly reduced on lesional compared to non-lesional skin [ 9 , 10 ] whereas other have found no difference in alpha diversity between the two skin sites [ 5 , 11 ]. These contradictory results may suggest a continuous transition between lesional and non-lesional skin within AD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the AD group consisted of infants who not necessarily had developed AD or had active disease at the sampling time-points, which very well can influence the results. S. aureus was not identified in any of the skin samples (36), despite the fact that S. aureus is frequently detected on antecubital and popliteal fossa skin regions in older children and adults with AD (8,10). Although this could indicate that S. aureus colonization at the antecubital and popliteal fossa is not an essential marker for AD during disease development in the first year of life, culture-based analysis has indicated the opposite (37).…”
Section: Box 2 Diversity and Taxonomy Analysismentioning
confidence: 99%
“…Furthermore, patients with AD have an increased burden of Staphylococcus aureus skin colonization, which is associated with disease severity and exacerbation (4)(5)(6)(7)(8). Within recent years, where it has become possible to examine complete microbial communities using advanced DNA sequencing technologies, it is evident that cutaneous S. aureus is associated with decreased bacterial diversity on AD skin (8)(9)(10)(11)(12)(13). The aim of this review is to provide an overview of the recent literature on the skin microbiome as well as microbe-host interactions in AD.…”
mentioning
confidence: 99%